Psychosocial Issues as a Determinant of Intimate Partner Violence among Married Adults in Ondo State - Michael, Ifeoluwa; Abisoye, Faysol (Buletin Konseling Inovatif, 2025)
This study examines psychosocial challenges and communication styles as predictors of domestic violence among married adults in Osun State, Nigeria. Utilizing a descriptive survey research design, the study aimed to explore the influence of psychosocial issues such as interference from in-laws, financial instability, and lack of emotional support on instances of intimate partner violence. It also investigated the role of communication styles, including assertiveness, conflict management, and relational dynamics, in mitigating or exacerbating domestic violence. A total of 400 married adults were selected using stratified random sampling from diverse demographic backgrounds. Data were collected through a validated questionnaire titled "Psychosocial and Relational Determinants of Domestic Violence (PRDDV)," which achieved a reliability coefficient of 0.78. Findings revealed a significant positive correlation between psychosocial challenges and the prevalence of domestic violence (r = 0.164, p < 0.05), while communication styles showed a moderating effect on the relationship. The study concluded that addressing psychosocial issues and promoting healthy communication styles could reduce domestic violence. Recommendations include targeted counseling programs, public awareness campaigns, and policy interventions aimed at fostering harmonious relationships among married adults. These findings are essential for counselors, social workers, and policymakers in developing evidence-based strategies to curb domestic violence.